THE INFLUENCE OF JOB SATISFACTION AND PSYCHOLOGICAL WELL BEING ON EMOTIONAL LABOR IN EMPLOYEES OF BANK BRI - Abdullah Umar Siregar; Suryani Hardjo; Kaiman Turnip (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The aim of this research is to determine the effect of job satisfaction and psychological well-being on the emotional labor of BRI employees. The research method used was quantitative. The population was 324 employees. 110 samples with purposive sampling technique. The data analysis technique used is multiple regression analysis technique. Based on the results of the first hypothesis testing, the regression value is 0.518 with sig <0.050, namely 0.001 <0.050, this value is equal to 51.8%, meaning there is a significant influence between job satisfaction and psychological well-being on surface action , with an influence size of 51.8%. Based on the results of testing the second hypothesis, the regression magnitude value was obtained, namely 0.678 with sig < 0.050, namely 0.001 < 0.050, this value is equal to 67.8%, meaning that there is a significant influence between job satisfaction and psychological well -being on deep action, with an influence magnitude of 67.8%. Based on the results of testing the third hypothesis, the regression value obtained is 0.664 with sig < 0.050, namely 0.001 < 0.050, this value is equal to 66.4%, meaning that there is a significant influence between job satisfaction and psychological well-being on action games, with an influence size of 66.4%.